PENGARUH FREKUENSI PENYAJIAN RANSUM YANG BERBEDA TERHADAP RASIO EFISIENSI PROTEIN, MASSA PROTEIN DAGING DAN MASSA KALSIUM DAGING AYAM KAMPUNG SUPER - Polbangtan, B. Wijayanto, U. Atmomarsono W. Sarengat (Jurnal Pengembangan Penyuluhan Pertanian, 2018)
ABSTRACT The research was aimed to evaluate the effect of different fedding frequencies to thequality of growth is protein efficiency ratio, meat protein mass and meat calcium mass ofcrossbred native chicken (male native chicken x female laying hen). The material used was 120 unsexed birds with average body weight 97,49 ± 5,40 g (CV = 12,4%), were kept until 7 weeks. The experiment was designed as completely randomized design with 4 treatmentsand 5 replications. There were 6 birds each per experiment. Treatments applied were T1(feeding a time a day, at 06.00 am), T2 feeding two times a day, at 06.00 am and 06.00pm), T3 (feeding three times a day, at 06.00 am, 12.00 am and 06.00 pm), T4 (feeding fourtimes a day, at 06.00 am, 12.00 am, 06.00 pm and 12.00 pm). Parameters measured wereprotein efficiency ratio, meat protein mass and meat calcium mass. Data were analyzedaccording to analysis of variance (ANOVA) determine the effect of treatment. Differentfeeding frequencies were not significant (P>0,05) on protein efficiency ratio, meat proteinmass and meat calcium mass. Conclusion of this research explain different feedingfrequencies against crossbred native chicken, didn’t change the rate of protein efficiencyratio, meat protein mass and meat calcium mass.